DAGESTAN ANTHROPONYMY IN THE LOCAL ARABIC-LANGUAGE WRITTEN TRADITION: SOME PRACTICAL ISSUES OF SOURCE STUDIES AND PUBLICATIONS - Musaev, Mahac Abdulaevic (History, Archeology and Ethnography of the Caucasus, 2023)
The Arabic language, which came to the East Caucasus along with Islam, with the intensification of Islamization processes became the language of writing for the region. It maintained this status until the end of the 1920s of the 20th century, fundamentally changing the local nomenclature of proper names and fully adapting their spelling to the already established rules of the Arabic anthroponymic system, the components of which were kunya, mansab, ism, nasab, nisba and lakab. Dagestan anthroponymy in local Arabic texts functioned according to the rules and within the framework of Arab-Islamic anthroponymy; however, it had a number of peculiarities. The basis of the Dagestan anthroponymicon was the names abbreviated to ‘urf, which was sufficient for identification. These are names consisting of a proper name, which often goes with a nasab, as well as a nisba, formed according to a geographical principle and attributing a person to their community (village) or union of communities. This form became the most common due to its similarity with the local Dagestan model of identification and self-identification. The experience of working with the Dagestan Arabic-language written heritage has allowed us to point out certain difficulties in reading and identifying local nisbas: the absence of Arabic equivalents of part of the letters of the Dagestan languages, the transformation of nisbas in time, the translation of nisbas’ meaning, their abbreviation, etc. This problem can be solved by compiling a dictionary of Dagestan nisbas, the model of which is proposed in our study. The paper also highlights the peculiarities of the denotation of Dagestan Arabic anthroponymy in Cyrillic: a combination of transliteration, transcription, etc., which, despite the contradiction, are often combined within the framework of a single publication. We propose to use a unified approach within the framework of one study, while the best way to convey Dagestan anthroponymy is to use the original Arabic script at the first mention, and later in the text to denote it with a simplified transcription as close as possible to the phonation in Dagestan languages.
Keywords: Dagestan anthroponymy; Arabic anthroponymy; written culture; nisba; anthroponymy; onomastics